Mental Health Analysis of Students Whose Parents are Divorce at Smp Negeri 25 Pekan Baru - Victoria, Ceria Galossa; Wangid, Muhammad Nur (World Psychology, 2025)
Divorce is a social phenomenon that not only changes the family structure, but also affects the roles, communication, and emotional balance within it. Children as the most vulnerable party in divorce often experience mental stress due to the separation of their parents, both directly and indirectly. descriptive method with a quantitative approach to understand the mental health of students whose parents are divorced The research was conducted at SMP Negeri 25 Pekanbaru, the subjects studied were 30 students whose parents were divorced. The data collection used a closed questionnaire, namely respondents were only asked to choose the available answers. To determine the score range according to the indicators given, it is divided into three categories, namely good, sufficient, and lacking. The results of the study conducted on 30 subjects at SMP Negeri 25 Pekanbaru showed that in general the mental health of students whose parents are divorced is in the good category. This means that students whose parents are divorced still have good mental health , the mental health of students in the psychological indicator is in the good category with a percentage of 67% including respect for themselves and others, having Insight and a sense of humor, having a reasonable emotional response, being able to think realistically and objectively, avoiding psychological disorders, being creative and innovative, being open and flexible, not defensive, having a feeling of freedom to choose, express opinions and act.